The Influence Analysis of Competence, Service Quality and Work Environment on Employee Performance with Motivation as an Intervening Variable in the Personnel and Human Resources Development Agency (BKPSDM) Batu City - Putri, Novita Rizky Elyani (International Journal of Business, Management and Economics, 2023)
The purpose of this study is to describe the impact of competence, quality of service, and work environment on employee performance with motivation as an intervening variable. Several analytical techniques were performed in this study and the analyzes were performed using his SEM data analysis technique using his AMOS application. Descriptive results for competency variables are consistent with the presence of traits in paying attention to employee autonomy in coping with stress, solving work problems, and working overtime. Skills to complete tasks and responsibilities are also approved by employees, and skills with employee confidence, expertise, and communication skills are also approved by Batu City BKPSDM employees. Different service quality pays average attention to reliability, responsiveness, courtesy and reliability, approved by her BKPSDM staff in Batu City to provide the best service in fulfilling duties and responsibilities to do. The physical and psychological work environment is also very influential in determining the performance of BKPSDM employees. This includes lighting work areas, providing good air circulation, avoiding conflicts between employees, and ensuring protection and safety from authorities. Performance variable success is also due to aspects of collaboration, responsibility, and goal attainment, while motivation variable success is done by considering motivations, expectations, and incentives. This is also endorsed by all employees of BKPSDM K Batu City i.e. competence. , Service quality and working environment can improve performance through motivation in BKPSDM Batu City. Competence, quality of service, and working environment have a significant impact on the performance of the Human Resources and Human Resources Development Board (BKPSDM) Batu City employees